Manufacturers’ Green Decision Evolution Based on Multi-Agent Modeling - Zhen Li; Hongming Zhu; Qingfeng Meng; Changzhi Wu; Jianguo Du (Complexity)
The development of green products is gradually becoming important due to serious ecological issues. In this study, an agent-based model is developed to visualize and analyze the evolution of green decision-making in the manufacturing industry. Based on this agent-based model, the macrobehaviors of manufacturers, consumers, and products are analyzed and simulated. Our results show that, first, the manufacturing industry emerges showing a “convergence” effect. The manufacturers may overestimate the consumers’ green degree demand, but this gradually gets corrected through the mechanisms of market competition. Second, as consumer income increases, it becomes easier for manufacturers to adapt to the market’s supply and demand as impacted by the products’ green degrees, and it becomes unfavorable for them to form a monopoly in the market. Furthermore, the profit of manufacturers is mainly derived from the sales and gradually gets more influenced by the products’ green degree when the consumer income increases.